(untitled) (Journal of Economics and Management Research, 2023)
ملخص: تهدف هذه الدراسة إلى تقييم دور الصناعة المالية الإسلامية في تعزيز الشمول المالي ، من خلال معرفة مختلف المنتجات التي تقدمها الصناعة المالية الاسلامية ضمن عملياتها وخدماتها المصرفية، وللوصول إلى الهدف السابق استخدمنا المنهج الاستنباطي بأداتيه الوصف والتحليل عبر مناقشة النقاط التالية: مفهوم الصناعة المالية الاسلامية والمنتجات التي تقدمها الصناعة المالية الاسلامية ، واقع الصناعة المالية الاسلامية في العالم ، واقع الشمول المالي في بعض دول العالم ثم واقع الصناعة المالية الاسلامية في الجزائر ودورها في تعزيز الشمول المالي خلصت الدراسة أن الصناعة المالية الإسلامية على غرار الدول الخليجية والسودانية وحتى الآسيوية خاصة ماليزيا واندونيسيا، عرفت تطورا كبيرا خاصة بعد الازمة المالية العالمية ولعبت دورا في تمويل التنمية وتعزيز الشمول المالي لهذه الدول. الكلمات المفتاحية : الصناعة المالية الاسلامية ، الشمول المالي، ازمات مالية. تصنيف JEL:G17،G32، G01 Abstract : This study aims to assess the role of the Islamic financial industry in promoting financial inclusion, by identifying the various products offered by the Islamic financial industry within its banking operations and services. To reach the previous goal, we used the deductive approach with its description and analysis tools by discussing the following points: The concept of the Islamic financial industry and the products it offers, the reality of the Islamic financial industry in the world, the reality of financial inclusion in some countries of the world and then the reality of the Islamic Financial industry in Algeria and its role in promoting financial inclusion. The study concluded that the Islamic financial industry experienced a major development after the global financial crisis like in the Gulf, Sudanese and even Asian countries, especially Malaysia and Indonesia. It played an important role in financing development and promoting the financial inclusion of these countries. Keywords: Islamic financial industry, financial inclusion, financial crises. JEL Classification Codes:G17 ,G32 ,G01